A Four-Year Video Monitoring Analysis of the Posidonia oceanica Banquette Dynamic: A Case Study from an Urban Microtidal Mediterranean Beach (Poetto Beach, Southern Sardinia, Italy) - Daniele Trogu; Simone Simeone; Andrea Ruju; Marco Porta; Angelo Ibba; Sandro DeMuro (Journal of Marine Science and Engineering, 2023)
This paper investigates the dynamics of the cross-shore extensions of banquettes, a sedimentary structure mostly made by rests of Posidonia oceanica (L.) Delile, in a sandy urban beach located in the Gulf of Cagliari, Italy, western Mediterranean. A video monitoring station was installed above the promontory south of the beach. We analysed a four-year image database and related these dynamics to wave and wind parameters (obtained from the Copernicus and ERA5 databases) from September 2016 to September 2020. Our results showed that banquette deposition occurred in concomitance with the presence of leaf litter in the surf zone associated with mild storm events. Erosion of the banquettes occurred during more intense storms. When leaf litter was not present in the surf zone, banquettes were not deposited even with mild storms. Wind can influence the banquette dynamics: under certain conditions of speed intensity, the banquettes may be removed offshore, supplying litter in the surf zone, or they may be covered by sediment. The permanence of the banquettes on the beaches also depended on their composition: when the banquettes were intertwined with reeds, their removal by the waves did not occur even during intense storms, and this sedimentary structure can protect the beach from flooding.